Self-assembly of Cu-TMA based semiconducting fibrous metallogels for fabrication of active electronic device with high rectification ratio - Kumar V.; Upadhyay R.K.; Bano D.; Chandra S.; Kumar Yadav P.; kumar D.; Jit S.; Hadi Hasan S. (My University, 2025)
A stable supramolecular Cu-TMA metallogel was synthesized by using Copper (II) acetate monohydrate and trimesic acid (TMA) as a low molecular weight organic gelator in DMF. The rheological studies confirmed that the synthesized Cu-TMA metallogels have high storage modular. The FT-IR (Fourier-transform infrared spectroscopy) and HR-MS (High Resolution Mass Spectrometry) analysis confirmed the metal–ligand aggregation in the produced metallogels. Apart, FESEM (Field Emission Scanning Electron Microscopy) and TEM (Transmission electron microscopy) probed the shape and morphology of the synthesized supramolecular metallogel like self-assembled fibrous like structure. However, TGA analysis confirmed the high thermal stability of metallogel. To explore the semiconducting properties of metallogel we calculate the energy band gap and, other electrical properties such as current–voltage characteristics and rectifying behaviour for metal–semiconductor (MS) junction-device have been properly investigated. In addition to this, based on the non-linear rectifying behaviour of the device, we have fabricated an active electronic device a Schottky Diode having high Rectification (Ion/Ioff) ratio. Consequently, our synthesized semiconducting Cu-TMA metallogel is fruitful and efficient and could be applied for various other optoelectronic devices in future. © 2023 Elsevier B.V.